2018
DOI: 10.1103/physreva.97.032118
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum rotation numbers of asymmetric-top molecules

Abstract: We study the classical and quantum rotation numbers of the free rotation of asymmetric top molecules. We show numerically that the quantum rotation number converges to its classical analog in the semi-classical limit. Different asymmetric molecules such as the water molecule are taken as illustrative example. A simple approximation of the classical rotation number is derived in a neighborhood of the separatrix connecting the two unstable fixed points of the system. Furthermore, a signature of the classical ten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…A large number of studies have shown the advantage of classical analysis for revealing the properties of quantum molecular spectra. This aspect has been investigated for the free molecular rotation [47,60,61,62,63,64,65], but also for molecules subject to a constant electric field [66,67,68]. Take Hamiltonian monodromy [57] as an example, which is the simplest topological obstruction to the existence of global action angle variables in classical integrable systems.…”
Section: Geometric Description Of Rotational Dynamicsmentioning
confidence: 99%
“…A large number of studies have shown the advantage of classical analysis for revealing the properties of quantum molecular spectra. This aspect has been investigated for the free molecular rotation [47,60,61,62,63,64,65], but also for molecules subject to a constant electric field [66,67,68]. Take Hamiltonian monodromy [57] as an example, which is the simplest topological obstruction to the existence of global action angle variables in classical integrable systems.…”
Section: Geometric Description Of Rotational Dynamicsmentioning
confidence: 99%
“…Clusters consisting of 2 and 3 nanotori were able to change their position twice during the considered period of time. Such a consistent change of positions has similar features to the flip effect of one body, which is described by the intermediate axis theorem [35][36][37][38]. Note that the classical intermediate axis theorem explains the case of unstable rotational motion of a body around an axis with an intermediate moment of inertia.…”
Section: Collective Behavior Of the Nanotori Clustermentioning
confidence: 78%
“…Different molecular systems could show traces of this effect at the quantum scale [20]. An example is given by asymmetric top molecules, such as the water molecule, which are the microscopic equivalent of asymmetric rigid bodies [21]. Another field of applications is the control of quantum systems by external electromagnetic fields [22] using, e.g., the analogy between Bloch and Euler equations [23].…”
mentioning
confidence: 99%

Geometric Origin of the Tennis Racket Effect

Mardesic,
Van Damme,
Guillen
et al. 2020
Preprint
Self Cite